WindowSense: A Smart Convenience Window - Yusof, Muhammad Hamizan; Mohd Nasir, Muhamad Izamuddin; Sujuanda, Syarifuddin; Soosay Nathan, Shelena (Multidisciplinary Applied Research and Innovation, 2024)
Smart windows are not totally a new idea, they have been developed by many companies nowadays. However, new developments in Internet of Things(IoT) technology have made it possible to produce smart windows that are more advanced and effective. Traditional window tends to face a lot of problems such as those that are related to bad weather, air quality, and user convenience. Hence, this study will identify the user requirements, developing the prototype of smart window and will evaluating the effectiveness of the developed prototype so that the user in residential area won’t face the problems with their window. Throughout this study, agile methodology is used because this method focuses on specific problem that need to be solved. The smart window will be installed with three different sensors which are gas sensor, rain drop sensor and lastly humidity sensor. These sensors respectively detects any change in environment so that the smart window will function accordingly. The developed smart window gains satisfaction from the user with the convenience and efficiency of the window. In the future, this study may be integrated with other smart home devices and system enhancing overall user efficiency and convenience.